Understanding what is visible in a mirror or through a window before and after updating the position of an object - Bertamini, Marco (Frontiers in Human Neuroscience, 2014)
In the Venus effect observers assume that Venus is admiring her own reflection in the mirror (Bertamini et al. 2003). However, since the observer sees her face in the mirror, Venus is actually looking at the reflection of the painter. This effect is general because it is not specific to paintings or to images of people. This study tests whether people have difficulties in estimating what is visible from a given viewpoint using a paper and pencil task. Participants (N=80) judged what is visible in a scene that could include a mirror or an aperture. The object in the scene (a train) was already located in front of the mirror or behind the aperture, or the same object had to be imagined to move to that location. The hypothesis was that this extra step (spatial transformation) is always part of how people reason about mirrors because they have to imagine the location of the reflection based on the location of the physical object. If so, this manipulation would equate the difficulty of the mirror and of the aperture conditions. Results show that performance on the paper and pencil task was better than expected, probably because of the asymmetric nature of the object used. However, an additional cost in reasoning about mirrors was confirmed.